Acute Intermittent Porphyria with SIADH and Fluctuating Dysautonomia - Nabin, A; Thapa, LJ; Paudel, R; Rana, PVS (Kathmandu University Medical Journal, 2013)
Three cases of acute intermittent porphyria are reported. While in first case severe pain in abdomen with intermittent exacerbation was the only presentation, the second patient presented as accelerated hypertension and acute abdominal crises in whom the clinical course was characterized by development of deep coma due to inappropriate secretion of antidiuretic hormone before she made complete recovery. The third patient, initially manifested as acute encephalitic syndrome. After initial improvement, she developed features of acute intermittent porphyria i.e. acute abdomen, neuropsychiatric symptoms, and rapidly progressing acute motor neuropathy leading to respiratory and bulbar paralysis. In addition, she developed severe and fluctuating dysautonomia leading to cardiac arrest and fatal termination. The importance of early diagnosis, recognition of autonomic disturbances, prompt treatment and counseling for avoidance of precipitating factors is stressed. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 96-99 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7354